2016
DOI: 10.1007/s11999-016-5039-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Risks and Costs of Care are Greater in Patients Who Are Super Obese and Undergoing THA

Abstract: Background Patients with morbid obesity, defined as a BMI greater than 40 kg/m 2 , and super obesity, defined as a BMI greater than 50 kg/m 2 , increasingly present for total hip replacement. There is disagreement in the literature whether these individuals have greater surgical risks and costs for the episode of care, and the magnitude of those risks and costs. There also is no established threshold for obesity as defined by BMI in identifying increased complications, risks, and costs of care. Until recently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 34 publications
1
46
2
1
Order By: Relevance
“…Data from the Danish registries demonstrated significantly higher mortality in underweight and normal BMI patients compared to overweight patients and suggested a BMI of 27-28 kg/m 2 was associated with the lowest risk of mortality 22 . In contrast with these findings and our own study, analysis of USA registers and a single center study of 1,744 patients in the UK observed no significant association between BMI and the risk of mortality [17][18][19][20][21] .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Data from the Danish registries demonstrated significantly higher mortality in underweight and normal BMI patients compared to overweight patients and suggested a BMI of 27-28 kg/m 2 was associated with the lowest risk of mortality 22 . In contrast with these findings and our own study, analysis of USA registers and a single center study of 1,744 patients in the UK observed no significant association between BMI and the risk of mortality [17][18][19][20][21] .…”
Section: Discussioncontrasting
confidence: 99%
“…Studies of BMI and mortality at 30-days, 90-days have shown mixed results. Four registry studies in the USA [17][18][19][20] and a single center study in the UK 21 (n=2,000 to 432,841), showed no significant association. Registry studies based in Denmark and the UK (n=34,000 and 410,000) have shown a protective effect of being overweight on 30-and 90-day mortality 4,22 .…”
Section: Introductionmentioning
confidence: 91%
“…Although there appeared to be strong consensus agreement, the social, political, and economic ramification of establishing an upper limit of the body mass index (BMI) threshold for elective surgery provoked strong arguments between delegates to the point that the question was removed without an official vote. Remarkably, subsequent high‐level peer‐reviewed research was published, which facilitated “unanimous” agreement for the 2018 ICM recommendations based on “Strong” and “Consensus” evidence of the risks (https://www.ors.org/wp-content/uploads/2019/01/BMI-Question.pdf). Other important outcomes of the 2013 ICM were: (i) an evidence‐based definition for hip and knee PJI that has been adopted by the Center for Disease Control (CDC), and (ii) several high‐impact publications as defined by over 1,000 downloads …”
Section: The Significance Of Mski In Terms Of Incidence Current and mentioning
confidence: 99%
“…research conducted among patients with different BMI (Body Mass Index) values underscores that people suffering from morbid obesity (BMI> 50) are exposed to significantly more serious postoperative complications, including the need for early reoperation, which entails higher costs [26]. According to retrospective studies that assess the presence of twelve increasingly serious complications during the first 90 days following surgery, patients with morbid obesity are much more likely to be exposed to implant infections, need for revision, wound dehiscence, deep vein thrombosis, pulmonary embolism, implant failure, acute renal failure, myocardial infarction and implant dislocation [27].…”
Section: Obesity In the Context Of Replacement Proceduresmentioning
confidence: 99%